Christus Vivit: Menggagas Peran Orang Muda yang Transformatif - Yuhanes Kristi Andayanto (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
The purpose of this essay is to explore the idea of transformative youth according to the Apostolic Exhortation of Pope Francis Christus vivit. This paper is designed as a study of official Church documents. Through a critical reading of this document, the author finds that transformative youth are those who dare to change their mindsets, have social commitments, and choose concrete attitudes and actions. Transformative youth have a spirituality of change and the power of change. In order to become agents of change, youth need to play an active and creative role in the pastoral work of the Church. Pope Francis' Apostolic Exhortation Christus Vivit motivates the whole transformative movement of youth.